Identifikasi Kemandirian Belajar Mahasiswa Program Studi Pendidikan Matematika Universitas Mathla’ul Anwar - Yunitasari, Ika (Universitas Mathla'ul Anwar Banten, 2024)
This research is motivated by the importance of self regulated learning to support the successful implementation of learning. Self regulated learning is the ability to organize oneself according to one's needs in studying subject matter. The aim of this research is to determine the level of self regulated learning of students in the Mathematics Education Study Program at Mathla'ul Anwar University. The subjects of this research were 29 students of the Mathematics Education Study Program, even semester in the 2023/2024 academic year. The research instrument is a self regulated learning questionnaire containing 20 questions using a Likert scale. The research method used is quantitative descriptive with data collection techniques using questionnaires. Data analysis was carried out using Microsoft Excel and the questionnaire scores were grouped into 5 categories, namely very high, high, medium, low and very low. From the research results it was found that as many as 3,4% of students had a very low level of self regulated learning, 24,1% of students had a low level of self regulated learning, 41,4% of students had a medium level of self regulated learning, 20,7% of students had a high level of self regulated learning, and 10,3% of students have a very high level of self regulated learning. Based on the research results, efforts are needed to increase students' independent learning attitudes so that the learning outcomes obtained are maximized